Low-dose thiamine supplementation of lactating Cambodian mothers improves human milk thiamine concentrations: a randomized controlled trial. Issue 1 (7th April 2021) - Gallant, Jelisa; Chan, Kathleen; Green, Tim J; Wieringa, Frank T; Leemaqz, Shalem; Ngik, Rem; Measelle, Jeffrey R; Baldwin, Dare A; Borath, Mam; Sophonneary, Prak; Yelland, Lisa N; Hampel, Daniela; et al.
ABSTRACT: Background: Infantile beriberi–related mortality is still common in South and Southeast Asia. Interventions to increase maternal thiamine intakes, and thus human milk thiamine, are warranted; however, the required dose remains unknown. Objectives: We sought to estimate the dose at which additional maternal intake of oral thiamine no longer meaningfully increased milk thiamine concentrations in infants at 24 wk postpartum, and to investigate the impact of 4 thiamine supplementation doses on milk and blood thiamine status biomarkers. Methods: In this double-blind, 4–parallel arm randomized controlled dose–response trial, healthy mothers were recruited in Kampong Thom, Cambodia. At 2 wk postpartum, women were randomly assigned to consume 1 capsule, containing 0, 1.2 (estimated average requirement), 2.4, or 10 mg of thiamine daily from 2 through 24 weeks postpartum. Human milk total thiamine concentrations were measured using HPLC. An Emax curve was plotted, which was estimated using a nonlinear least squares model in an intention-to-treat analysis. Linear mixed-effects models were used to test for differences between treatment groups. Maternal and infant blood thiamine biomarkers were also assessed. Results: In total, each of 335 women was randomly assigned to1 of the following thiamine-dose groups: placebo ( n =  83), 1.2 mg ( n =  86), 2.4 mg ( n =  81), and 10 mg ( n =  85). The estimated dose required to reach 90% of the maximum average total thiamine concentration in human milk (191 µg/L) is 2.35 (95% CI: 0.58, 7.01) mg/d. The mean ± SD milk thiamine concentrations were significantly higher in all intervention groups (183 ± 91, 190 ± 105, and 206 ± 89 µg/L for 1.2, 2.4, and 10 mg, respectively) compared with the placebo group (153 ± 85 µg/L; P  < 0.0001) and did not significantly differ from each other. Conclusions: A supplemental thiamine dose of 2.35 mg/d was required to achieve a milk total thiamine concentration of 191 µg/L. However, 1.2 mg/d for 22 wk was sufficient to increase milk thiamine concentrations to similar levels achieved by higher supplementation doses (2.4 and 10 mg/d), and comparable to those of healthy mothers in regions without beriberi. This trial was registered at clinicaltrials.gov as NCT03616288.